Here and now, there and then: How "departure dates" influence climate change engagement. (May 2016) - Rickard, Laura N.; Yang, Z. Janet; Schuldt, Jonathon P.
Highlights: We examine whether 'departure dates' influence climate change policy support. Manipulation framed climate change as occurring spatially/temporally near or far. Exposure to information interacted with political orientation. Spatial proximity and temporal distance mattered for U.S. conservatives. Results support research in psychological distance and climate change engagement. Abstract: Climate change alters landscapes, challenges economic systems, and threatens human and environmental health. Yet, despite real and present impacts, climate change remains largely an abstract risk to most people in the U.S. Using a survey with an embedded experiment, we explore responses to messages about climate "departure dates" by manipulating the spatial and temporal dimensions of future climate change impacts in two exemplar cities (New York City and Singapore) among U.S. and Singapore participants. Overall, results suggest that the influence of temporal and spatial features of departure dates is moderated by participants' political orientation and geographic location. For instance, we observed some of the largest effects of our manipulation on the reported policy support of conservatives in the U.S. as compared to U.S. liberals and their counterparts in Singapore. We draw connections to relevant theory (e.g., construal level theory) and consider implications for climate departure dates as communication devices.